Evaluation the implementation of the regional government accounting information system - Tuti Dharmawati; Hasbudin Hasbudin; Muhammad Jufrianci Dewa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aims to determine the implementation of the regional government accounting information system. This paper is a descriptive analysis with a qualitative approach. In data collection, interview and documentation techniques were employed. The results of this study indicate that the Accounting Information System (AIS) applied by the Kendari City has not been implemented optimally. It is proven that has not carried out its financial report input independently using the SIMDA Finance application. Instead, the authorized officer still went to the Kendari BPKAD office.